The need for inclusive agricultural growth at the heart of Africa's economic transition - (:unkn) unknown (My University, 2011)
The rapid increase in its population has confronted Africa with the necessity of engaging in a strong process of sustainable economic growth, while relying on activities that are not very competitive in an international economic context that is highly so. Agriculture will remain the leading source of employment and income in Africa for decades to come, and thus it is vital to introduce government policies conducive to inclusive agricultural growth, drawing on the full range of market opportunities, while ensuring that the majority of producers are not left behind.
Keywords: African Research